2014
DOI: 10.1007/s00383-014-3592-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality in children with typhoid ileal perforation in a Nigerian tertiary hospital

Abstract: The patients' age and postoperative burst abdomen were significant determinants of survival in children with typhoid ileal perforation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 13 publications
3
13
0
2
Order By: Relevance
“…Our findings showed that when the aetiology of surgical abdomen was matched with age groups and gender of our patients, the relative frequency of the various causes was consistent with earlier reports was obtained [1][2][3][7][8][9][10][11] . Patients below five years were excluded from the study as most of them were referred directly to the specialist paediatrics surgery unit where better ancillary support [intensive care unit and paediatrics anaesthetists] services were available.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our findings showed that when the aetiology of surgical abdomen was matched with age groups and gender of our patients, the relative frequency of the various causes was consistent with earlier reports was obtained [1][2][3][7][8][9][10][11] . Patients below five years were excluded from the study as most of them were referred directly to the specialist paediatrics surgery unit where better ancillary support [intensive care unit and paediatrics anaesthetists] services were available.…”
Section: Discussionsupporting
confidence: 91%
“…Thus surgical site infection occurring as the most common post-operative complication was not surprising in patients with intra-abdominal sepsis when compared with other causes of surgical abdomen in this study. The high rate of surgical site infection amongst patients with complicated intra-abdominal sepsis, like typhoid ileal perforation, corroborates earlier reports 8,10,11,13,15 . Furthermore patients with typhoid ileal perforation constituted the bulk of patients with post-operative complications; this may be due to the pan-systemic nature of the disease with septicaemia.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations